THE IMPORTANCE OF TRAVEL AND TOURISM IN FORMING A HEALTHY LIFESTYLE IN HIGH SCHOOL STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Education of the developed generation, and on this basis scientific substantiation of cultural and moral education of a healthy lifestyle in the development of social relations, analysis of the study of lifestyle thanks to independence is an urgent task.Modernization of the country thanks to independence and the creation of decent living conditions for the population, the development of a variety of works to create a healthy lifestyle.